Structural connectivity analyses in motor recovery research after stroke - Koch, Philipp (Ann Clin Transl Neurol, 2016)
Structural connectivity analyses by means of diffusion‐weighted imaging have substantially advanced the understanding of stroke‐related network alterations and their implications for motor recovery processes and residual motor function. Analyses of the corticospinal tract, alternate corticofugal pathways as well as intrahemispheric and interhemispheric corticocortical connections have not only been related to residual motor function in cross‐sectional studies, but have also been evaluated to predict functional recovery after stroke in longitudinal studies. This review will consist of an update on the available literature about structural connectivity analyses after ischemic motor stroke, followed by an outlook of possible future directions of research and applications.